2020
DOI: 10.3389/fpls.2020.592591
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Profile of Xylem Sap in Cotton Seedlings Is Changed by K Deficiency

Abstract: Xylem sap, belonging to the plant apoplast, not only provides plant tissues with inorganic and organic substances but also facilitates communication between the roots and the leaves and coordinates their development. This study investigated the effects of potassium (K) deficiency on the morphology and the physiology of cotton seedlings as well as pH, mineral nutrient contents, and metabolites of xylem sap. In particular, we compared changes in root–shoot communication under low K (LK) and normal K (NK, control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…This indicates that low-K + stress significantly reduced seedling biomass. In green plants, photosynthesis is an important process that provides the necessary energy sources for metabolism ( Chen et al, 2015 ; Zhang et al., 2020 ). Low-K + stress inhibits the photosynthetic activity of plants, leading to slower metabolism, thus affecting plant growth and development ( Kanai et al., 2011 ; Amanullah.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This indicates that low-K + stress significantly reduced seedling biomass. In green plants, photosynthesis is an important process that provides the necessary energy sources for metabolism ( Chen et al, 2015 ; Zhang et al., 2020 ). Low-K + stress inhibits the photosynthetic activity of plants, leading to slower metabolism, thus affecting plant growth and development ( Kanai et al., 2011 ; Amanullah.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomic analysis is used to detect metabolites in cells or tissues, study the synthesis of all or some metabolites, and elucidate their decomposition or transformation principles ( Hall, 2011 ; Zhang et al., 2020 ). Abiotic stress can lead to metabolic disorders in plants ( Meena et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nutrient deficiency is another kind of abiotic stress, and Ref. [85] showed that K deficiency reduced the antioxidant capacity of cotton seedlings and resulted in a metabolic disorder characterized by elevated levels of primary metabolites and reduced production of secondary metabolites. The results were from an analysis of xylem sap.…”
Section: Abiotic Stressesmentioning
confidence: 99%
“…K + is involved in multiple abiotic and biotic stresses [18,19,20]. K + transport participates in abiotic stress responses; the KT/HAK/KUP family genes are differentially responsive to drought and salt stresses [21,22].…”
Section: Introductionmentioning
confidence: 99%